Antagonism of Bacillus safensis strain against phytopathogenic bacteria - Olivella, Laura (2021)
Citrus canker caused by Xanthomonas citri subsp. citri (Xcc), is a bacterial disease which affects all the citrics. One alternative to manage it is the use of antagonist bacteria. The aim of this work was to investigate the antagonist activity of Bacillus safensis (S9) against Xcc. The activity was tested by diffusion assays. Xcc and S9 were grown overnight in Luria Bertani (LB) and potato dextrose (PD) medium, respectively, with continuous agitation at 28°C and then, were diluted to a concentration of 108 CFU/mL. Petri dishes were covered with 15 mL of LB-agar containing 100 μL of the Xcc dilution. Once the medium was solidified, 4 μL drops of S9 were inoculated 3 times in each Petri dish, and the experiment was made by triplicate. After 48 hours of incubation at 28°C, the inhibition zone was measured, and the average inhibition area was calculated as IA = average area of the inhibition zone - average area of the colony. A significant inhibition area of 5.18 cm2 was obtained (one-sample t- test, p<0.05). At the same time, diffusion assays with the supernatant were made to prove its inhibitory ability. Petri dishes were prepared as described above. The supernatant was obtained by centrifugation of the S9 culture grown in PD medium, and then by bacteria filtration. Three filter paper discs embedded with the supernatant were placed per Petri dish, by triplicate. The inhibition zone was measured after 48 hours and calculated the IA. A significant inhibition area of 2.29 cm2 was obtained (one-sample t-test, p<0.05). Besides, a study at genomic level comparing S9 with ten Bacillus strains was made. Different clusters of secondary metabolite synthesis pathways were detected, three common with B. velezensis strains (surfactin, basilicin and bacilibactin). These strains were tested as inhibitors of Xcc and they did not show inhibition (Bacillus sp and B. megaterium) or showed less inhibition (B. velezensis). The difference might be on the expression level of the clusters. These results suggest the potential use of S9 as a canker control agent and further studies will be necessary to identify the Xcc- inhibitor metabolite.